The Internet of Things and economic growth in a panel of countries. Issue 3 (3rd April 2021) - Edquist, Harald; Goodridge, Peter; Haskel, Jonathan
ABSTRACT: Is the world on the cusp of a fourth industrial revolution driven by technological developments in ICT including artificial intelligence and the Internet of Things (IoT)? This paper focuses on IoT and how it might affect economic growth. We attempt to gauge the potential impact of IoT using: (1) regressions based on current IoT data; and (2) longer run estimates of growth accounting parameters based on those observed in a previous wave of the ICT-revolution. We find that: (a) according to definitions in the literature, IoT is an innovational complementarity to ICT; (b) early data already suggest an economically and statistically significant correlation between IoT connections and TFP growth, implying that an increase of 10 percentage points in the growth of IoT connections per inhabitant is associated with a 0.23 percentage points increase in TFP growth; (c) longer run predictions of the IoT contribution based on a growth-accounting framework suggest a potential global annual average contribution to growth of 0.99% per annum (pa) in 2018–2030, approximately $849 billion pa of world GDP in 2018 prices.